(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
The article examines how “equity in healthcare” contributes to realizing “equity in health”, with particular regard to the role played by administrative planning and organization. After an outline of the principles that inspire the Italian healthcare system, it focuses on the essential levels of healthcare, which should ensure uniformity in health protection in the whole territory. Some of the included services show a particular attention to equity, like screenings or integrated care services, whose beneficiaries are vulnerable individuals. However, notwithstanding the definition of the essential levels, inequalities continue, as it emerges from the analysis of three critical issues: co-payment, waiting lists and the North-South divide in health protection. Consequences can be severe: the most disadvantaged slice of the population quite often foregoes treatment. The paper aims at highlighting how solutions for these problems depend not only on available economic resources, but also on organizational settings. Finally, some reflections concern how planning and organization of equity affect freedom of self-determination as to health treatment.